A low water absorption high performance flame retardant high temperature nylon composite and preparation method thereof
By using a combination of polyterephthalamide resin and glass fiber and other materials, a low-water absorption high-performance flame-retardant high-temperature nylon composite was prepared, which solved the water absorption, mechanical properties and flame-retardant properties of existing nylon composite materials. Inadequate, multiple performance improvements have been achieved.
Patent Information
- Application Number
- CN202310140413.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-02-21
AI Technical Summary
The existing nylon composite materials have shortcomings in water absorption, mechanical properties and flame retardant properties, and it is difficult to meet the requirements of low water absorption, high mechanical properties, high notch impact strength and flame retardant properties at the same time.
Polyterephthalamide resin (combination of PA6T resin and PA9T resin or PA10T resin) with glass fiber, flame retardant, antioxidant and lubricant, melt mixing through a twin-screw extruder to prepare low-quality Water absorption high performance flame retardant high temperature nylon composite.
The nylon composite has achieved low water absorption rate, good mechanical properties, high reflow resistance welding temperature and high flame retardant properties, and avoids bubbles caused by water absorption.
Smart Images

Figure BDA0004087279920000071 
Figure BDA0004087279920000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer composite materials, in particular to IPC C08L77, and further to a low water absorption, high performance, flame retardant, high temperature nylon composite. Background Art
[0002] Nylon has been widely used in the fields of automobiles, electronics, machinery, etc. due to its high mechanical strength, high melting point, wear resistance, oil resistance, and heat resistance. However, due to its high water absorption, the product has poor dimensional stability and reduced mechanical strength.
[0003] Chinese patent CN 201480030967 discloses a flame retardant high temperature nylon composite, using a flame retardant high temperature nylon composite with non-halogenated components. Polyphenylene ether, or optionally a combination of polyphenylene ether and bismaleimide, acts as a synergist with polyphosphate to achieve a V0 rating in the UL94 test at a thickness of about 3.18 mm, preferably about 1.59 mm. Chinese patent CN201510557447 discloses a thermally conductive high temperature nylon composite material and a preparation method thereof, which is composed of the following components by mass percentage: PPA resin: 19-47%; halogen-free flame retardant: 20-30%; liquid fire retardant oil: 0-5%; thermally conductive filler: 30-40%; coupling agent: 1-2%; antioxidant: 1-2%; lubricant: 1-2%. The nylon composite material of the present invention has good thermal conductivity and high flame retardancy, and can meet the requirements of EU standard flame retardant materials without halogenation. However, the technical problems solved by the above technical solutions are its high temperature resistance and flame retardancy, while the water absorption performance has not been studied; and its mechanical properties also need to be improved; the above technical solutions cannot simultaneously satisfy the nylon composite's low water absorption rate, high mechanical properties, high notch impact strength and flame retardancy. Summary of the invention
[0004] In order to solve the above technical problems, the first aspect of the present invention provides a low water absorption, high-performance, flame-retardant, high-temperature nylon composite. The raw materials include, by weight: 40 to 60 parts of polyterephthalamide resin, 15 to 40 parts of glass fiber, 10 to 20 parts of flame retardant, 0.4 to 1.6 parts of antioxidant, and 0.2 to 0.5 parts of lubricant.
[0005] In some preferred embodiments, the polyterephthalamide resin is selected from one or more combinations of PA6T resin, PA9T resin, PA10T resin, PA11T resin, PA12T resin, and PA13T resin.
[0006] Preferably, the polyterephthalamide resin is a combination of PA6T resin and PA9T resin or a combination of PA6T resin and PA10T resin.
[0007] Preferably, the weight ratio of the PA6T resin to the PA9T resin is (0.5-2): (0.5-2).
[0008] Preferably, the weight ratio of the PA6T resin to the PA10T resin is (0.5-2): (0.5-2).
[0009] In some preferred embodiments, the melt flow rate of the PA9T resin is 10 to 20 g / 10 min (320° C., 2.16 kg).
[0010] In some preferred embodiments, the melt flow rate of the PA10T resin is 10 to 20 g / 10 min (330° C., 1.2 kg).
[0011] In the present invention, when the polyterephthalamide resin is a combination of PA6T resin and PA9T resin or a combination of PA10T resin, and the weight ratio of PA6T resin to PA9T resin is controlled to be (0.5-2): (0.5-2); the weight ratio of PA6T resin to PA10T resin is (0.5-2): (0.5-2), the advantages of high strength and good heat resistance of PA6T and low water absorption of PA9T and PA10T are combined, and the prepared nylon composite has good mechanical properties, low water absorption and high reflow soldering temperature resistance after water absorption, which can effectively avoid the blistering phenomenon of pure PA6T resin material during the reflow soldering process due to too high water absorption. The inventors speculate that when PA6T resin is blended with PA9T resin or PA10T resin, PA9T resin and PA10T resin have lower water absorption and can be dispersed in PA6T resin. The proportion of amide groups in the nylon composite is smaller, which reduces the probability of amide groups forming hydrogen bonds with water. Therefore, the absorption and penetration of water molecules by the nylon composite can be reduced, thereby playing a structural shielding role. The dimensional stability of the product of the nylon composite with high water absorption is lower during the molding process, and the mechanical properties of the product will decrease after absorbing water, and the water absorption will cause the product to have adverse effects such as blistering and discoloration during the reflow soldering process. The polyterephthalamide resin of the present invention is a combination of PA6T resin and PA9T resin or a combination of PA6T resin and PA10T resin, which can improve the dimensional stability and mechanical properties of the product of the nylon composite during the molding process, and effectively avoid the blistering phenomenon of the pure PA6T resin material during the reflow soldering process due to the high water absorption. The inventors It was further found that when the melt flow rate of PA9T resin is 10-20 g / 10 min (320°C, 2.16 kg); when the melt flow rate of PA10T resin is 10-20 g / 10 min (330°C, 1.2 kg), the mechanical properties of the nylon composite can be further improved. The inventors speculate that when the melt flow rate of PA9T resin and PA10T resin is low, the shearing effect of the screw on the resin and glass fiber is large during the twin-screw extrusion process, thereby reducing the reinforcement effect. As the melt flow rate of PA9T resin and PA10T resin increases, the shearing effect of the screw on the resin and glass fiber is small, thereby improving the reinforcement effect and the mechanical properties of the nylon composite. However, when the melt flow rate of PA9T resin and PA10T resin is high, the strength provided by the PA9T resin and PA10T resin themselves is low, which causes the mechanical properties of the nylon composite to decrease to a certain extent.When the melt flow rate of the PA9T resin in the system of the present invention is controlled to be 10-20 g / 10 min (320° C., 2.16 kg); and the melt flow rate of the PA10T resin is controlled to be 10-20 g / 10 min (330° C., 1.2 kg), the strength provided by the polyterephthalamide resin itself can be ensured, and the reinforcing effect of the glass fiber on the polyterephthalamide resin can be improved, thereby improving the mechanical properties of the nylon composite.
[0012] In some preferred embodiments, the glass fibers are selected from chopped glass fibers or long glass fibers.
[0013] Preferably, the glass fibers are chopped glass fibers.
[0014] Preferably, the chopped length of the chopped glass fibers is 1 to 10 mm.
[0015] More preferably, the chopped length of the chopped glass fibers is 2 to 4 mm.
[0016] Further preferably, the surface of the chopped glass fibers is coated with a silane-based sizing agent.
[0017] The inventors have found that when the glass fibers are chopped glass fibers, especially when the chopped length of the chopped glass fibers is 2 to 4 mm and the surface is coated with a silane-based impregnating agent, the prepared nylon composite has good mechanical properties, low water absorption and high heat deformation temperature. The inventors speculate that glass fibers can form a skeleton in a polyterephthalamide resin matrix. When subjected to external force, the force is transmitted along the direction of the fiber orientation from the matrix to the glass fibers, thereby enhancing the ability of the nylon composite to withstand external force and improving its mechanical properties. The chopped glass fibers with a chopped length of 2 to 4 mm and a silane-based sizing agent coated on the surface can be dispersed more evenly in the polyterephthalamide resin matrix, and can form a more sufficient bonding force with the polyterephthalamide resin. Moreover, the covalent bond molecular layer formed on the surface of the chopped glass fibers coated with a silane-based sizing agent can prevent moisture from invading, thereby improving the mechanical properties of the nylon composite and reducing water absorption. In addition, the chopped glass fibers have a high melting point. At the thermal deformation temperature of the polyterephthalamide resin, the chopped glass fibers can still maintain their original shape, hindering the movement of the molecular chains of the polyterephthalamide resin, thereby increasing the thermal deformation temperature of the nylon composite.
[0018] In some preferred embodiments, the flame retardant is selected from one or more combinations of diethyl aluminum hypophosphite, aluminum hydroxide, magnesium hydroxide, and tricresyl phosphate.
[0019] In some preferred embodiments, the antioxidant includes hindered phenol antioxidants and SEED antioxidants.
[0020] Preferably, the mass ratio of the hindered phenol antioxidant to the SEED antioxidant is (1-4): (1-4).
[0021] In some preferred embodiments, the lubricant is selected from at least one of modified high molecular weight silicone, ethylene acrylic acid copolymer, and pentaerythritol stearate.
[0022] The second aspect of the present invention provides a method for preparing a low water absorption, high performance, flame retardant, high temperature nylon composite, comprising the following steps: melt mixing polyterephthalamide resin, glass fiber, flame retardant, antioxidant, and lubricant by weight through a twin-screw extruder, and extruding and granulating to obtain the composite.
[0023] Preferably, the aspect ratio of the twin-screw extruder is 44 to 52:1.
[0024] Preferably, the glass fiber is added from the 5th barrel section of the twin-screw extruder by a side feeder, and the flame retardant is added from the 8th barrel section of the twin-screw extruder by a side feeder.
[0025] Preferably, the temperature of the twin-screw extruder is: 240-260°C for the first section, 290-310°C for the second section, 310-320°C for the third section, 310-320°C for the fourth section, 300-320°C for the fifth section, 290-310°C for the sixth section, 270-290°C for the seventh section, 250-270°C for the eighth section, 220-240°C for the ninth section, and 190-210°C for the tenth section; the die head temperature is 300-320°C.
[0026] Preferably, the twin-screw main engine has a rotation speed of 400-600 r / min.
[0027] Beneficial effects:
[0028] 1. In the present invention, when the weight ratio of PA6T resin to PA9T resin is (1-1.5): (1-1.5); the weight ratio of PA6T resin to PA10T resin is (1-1.5): (1-1.5), the advantages of high strength and good heat resistance of PA6T and low water absorption of PA9T and PA10T are combined, the prepared nylon composite has good mechanical properties, low water absorption and high reflow soldering temperature resistance after water absorption, which can effectively avoid the blistering phenomenon of pure PA6T resin material during the reflow soldering process due to too high water absorption.
[0029] 2. In the present invention, when the melt flow rate of PA9T resin is 10-20 g / 10 min (320°C, 2.16 kg); when the melt flow rate of PA10T resin is 10-20 g / 10 min (330°C, 1.2 kg), PA9T resin and PA10T resin themselves have high strength and will not cause excessive shearing effect of the screw on the resin and glass fiber, and have good reinforcement effect, thereby improving the mechanical properties of the nylon composite.
[0030] 3. In the present invention, when the chopped length of the short glass fibers is 2 to 4 mm, they can be dispersed more evenly in the polyterephthalamide resin matrix and can form a more sufficient bonding force with the polyterephthalamide resin, thereby improving the mechanical properties of the nylon composite and reducing the water absorption rate; in addition, the short glass fibers have a high melting point, and at the thermal deformation temperature of the polyterephthalamide resin, the short glass fibers can still maintain their original shape, hindering the movement of the polyterephthalamide resin molecular chains, thereby increasing the thermal deformation temperature of the nylon composite.
[0031] 4. The present invention selects short glass fibers coated with a silane-based sizing agent on the surface, which can enhance the interfacial adhesion between the glass fibers and the polyterephthalamide resin matrix on the one hand; on the other hand, the covalent bond molecular layer formed on the surface can prevent moisture intrusion, further improve the mechanical properties of the nylon composite and reduce water absorption.
[0032] 5. The present invention controls the speed of the twin-screw main engine to 400-600 r / min, which can make the retention length of the chopped glass fibers longer, improve the orderliness of the distribution of the chopped glass fibers, and avoid the aggregation of the chopped glass fibers in the polyterephthalamide resin matrix, which affects the mechanical properties of the nylon composite. DETAILED DESCRIPTION
[0033] Example 1
[0034] Example 1 provides a low water absorption, high performance, flame retardant, high temperature nylon composite, wherein the raw materials include, by weight: 53.7 parts of polyterephthalamide resin, 30 parts of glass fiber, 15 parts of flame retardant, 1.1 parts of antioxidant, and 0.2 parts of lubricant.
[0035] The polyterephthalamide resin is a combination of PA6T resin and PA9T resin.
[0036] The weight ratio of the PA6T resin to the PA9T resin is 0.79:1.
[0037] The model of the PA6T is: Japan Mitsui AE4200.
[0038] The melt flow rate of the PA9T resin is 12 g / 10 min (320° C., 2.16 kg), and the model is Japan Kuraray N1001A.
[0039] The glass fibers are chopped glass fibers.
[0040] The chopped length of the chopped glass fibers is 3±1 mm.
[0041] The surface of the chopped glass fibers is coated with a silane-based sizing agent, model: China Jushi 568H.
[0042] The flame retardant is diethyl aluminum hypophosphite.
[0043] The antioxidants include 1098 antioxidant and SEED antioxidant.
[0044] The mass ratio of the 1098 antioxidant to the SEED antioxidant is 1:1.
[0045] The lubricant is pentaerythritol stearate.
[0046] A method for preparing a low water absorption, high performance, flame retardant, high temperature nylon composite comprises the following steps: melt mixing polyterephthalamide resin, glass fiber, flame retardant, antioxidant and lubricant by weight through a twin-screw extruder, and extruding and granulating to obtain the composite.
[0047] The length-to-diameter ratio of the twin-screw extruder is 50:1.
[0048] The chopped glass fibers are added from the 5th barrel of the twin-screw extruder by a side feeder, and the flame retardant is added from the 8th barrel of the twin-screw extruder by a side feeder.
[0049] The temperature of the twin-screw extruder is: 250°C for the first section, 300°C for the second section, 315°C for the third section, 315°C for the fourth section, 310°C for the fifth section, 300°C for the sixth section, 280°C for the seventh section, 260°C for the eighth section, 230°C for the ninth section and 200°C for the tenth section; the die head temperature is 310°C.
[0050] The twin-screw main engine has a rotation speed of 500 r / min.
[0051] Example 2
[0052] Example 2 provides a low water absorption, high performance, flame retardant, high temperature nylon composite, wherein the raw materials include, by weight: 53.7 parts of polyterephthalamide resin, 30 parts of glass fiber, 15 parts of flame retardant, 1.1 parts of antioxidant, and 0.2 parts of lubricant.
[0053] The polyterephthalamide resin is a combination of PA6T resin and PA10T resin.
[0054] The weight ratio of the PA6T resin to the PA10T resin is 0.79:1.
[0055] The model of the PA6T is: Japan Mitsui AE4200.
[0056] The melt flow rate of the PA10T resin is 17 g / 10 min (330° C., 1.2 kg), and the model is Wison Resin H101.
[0057] The glass fibers are chopped glass fibers.
[0058] The chopped length of the chopped glass fibers is 3±1 mm.
[0059] The surface of the chopped glass fibers is coated with a silane-based sizing agent, model: China Jushi 568H.
[0060] The flame retardant is diethyl aluminum hypophosphite.
[0061] The antioxidants include 1098 antioxidant and SEED antioxidant.
[0062] The mass ratio of the 1098 antioxidant to the SEED antioxidant is 1:1.
[0063] The lubricant is pentaerythritol stearate.
[0064] A method for preparing a low water absorption, high performance, flame retardant, high temperature nylon composite comprises the following steps: melt mixing polyterephthalamide resin, glass fiber, flame retardant, antioxidant and lubricant by weight through a twin-screw extruder, and extruding and granulating to obtain the composite.
[0065] The length-to-diameter ratio of the twin-screw extruder is 50:1.
[0066] The chopped glass fibers are added from the 5th barrel of the twin-screw extruder by a side feeder, and the flame retardant is added from the 8th barrel of the twin-screw extruder by a side feeder.
[0067] The temperature of the twin-screw extruder is: 250°C for the first section, 300°C for the second section, 315°C for the third section, 315°C for the fourth section, 310°C for the fifth section, 300°C for the sixth section, 280°C for the seventh section, 260°C for the eighth section, 230°C for the ninth section and 200°C for the tenth section; the die head temperature is 310°C.
[0068] The twin-screw main engine has a rotation speed of 500 r / min.
[0069] Example 3
[0070] Example 3 provides a low water absorption, high performance, flame retardant, high temperature nylon composite, the specific implementation of which is the same as that of Example 1, except that the weight ratio of the PA6T resin to the PA9T resin is 1.685:1.
[0071] Example 4
[0072] Example 4 provides a low water absorption, high performance, flame retardant, high temperature nylon composite, the specific implementation of which is the same as that of Example 1, except that the polyterephthalamide resin is PA6T resin.
[0073] Example 5
[0074] Example 5 provides a low water absorption, high performance, flame retardant, high temperature nylon composite, the specific implementation of which is the same as that of Example 2, except that the melt flow rate of the PA10T resin is 0.6 g / 10 min (330° C., 1.2 kg), model: Wison Resin H211.
[0075] Example 6
[0076] Example 6 provides a low water absorption, high performance, flame retardant, high temperature nylon composite, the specific implementation of which is the same as that of Example 1, except that the short chopped glass fiber is replaced with long glass fiber, model: China Jushi 910.
[0077] Performance Testing:
[0078] 1. Tensile strength: refer to ASTM D638 standard.
[0079] 2. Flexural strength: refer to ASTM D638 standard.
[0080] 3. Notched impact strength: refer to ASTM D638 standard.
[0081] 4. Flame retardancy (1.6mm): Refer to UL94 standard.
[0082] 5. Heat deformation temperature: refer to ASTM D648 standard.
[0083] 6. Water absorption rate: Make a sample strip with a length of 125mm, a width of 13mm and a thickness of 1.6mm, put the sample strip into an oven and bake it at 140℃ for 4 hours, then put the sample strip into water and boil it for 3 hours. After taking it out, naturally dry the moisture on the surface of the sample strip, and then use a moisture tester to test the moisture content of the sample strip, which is the water absorption rate of the product.
[0084] 7. Reflow resistance temperature after water absorption: Put the boiled sample into the reflow equipment, set the temperature of each section of reflow, the total time is about 7 minutes, check whether there is blistering on the surface of the sample after reflow, if there is blistering, reduce the temperature of each section of reflow by 5℃ and measure again until the sample does not bubble. The highest temperature without blistering is the reflow resistance temperature of the sample after water absorption.
[0085] Table 1:
[0086]
[0087]
Claims
1. A low water absorption, high performance, flame retardant, high temperature nylon composite, characterized in that: The raw materials include, by weight: 40-60 parts of polyterephthalamide resin, 15-40 parts of glass fiber, 10-20 parts of flame retardant, 0.4-1.6 parts of antioxidant, and 0.2-0.5 parts of lubricant; The polyterephthalamide resin is a combination of PA6T resin and PA9T resin or a combination of PA6T resin and PA10T resin; The weight ratio of the PA6T resin to the PA9T resin is (0.5-2): (0.5-2); the weight ratio of the PA6T resin to the PA10T resin is (0.5-2): (0.5-2); The melt flow rate of the PA9T resin is 10-20 g / 10 min; The melt flow rate of the PA10T resin is 10-20 g / 10min; The glass fibers are selected from chopped glass fibers; The method for preparing the low water absorption high-performance flame-retardant high-temperature nylon composite comprises the following steps: melt-mixing polyterephthalamide resin, glass fiber, flame retardant, antioxidant and lubricant by weight through a twin-screw extruder, and extruding and granulating to obtain the composite; The main engine speed of the twin-screw extruder is 400-600 r / min.
2. The low water absorption high performance flame retardant high temperature nylon composite according to claim 1, characterized in that: The length of the chopped glass fibers is 1 to 10 mm.
3. The low water absorption high performance flame retardant high temperature nylon composite according to claim 1, characterized in that: The flame retardant is selected from one or more combinations of diethyl aluminum hypophosphite, aluminum hydroxide, magnesium hydroxide, and tricresyl phosphate.
4. A method for preparing a low water absorption, high performance, flame retardant, high temperature nylon composite according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: polyterephthalamide resin, glass fiber, flame retardant, antioxidant and lubricant are melt-mixed by weight through a twin-screw extruder, and then extruded and granulated to obtain the product.
Citation Information
Patent Citations
Heat-conducting high-temperature nylon composite material and preparation method thereof
CN105038219A
Flame retardant high temperature nylon
CN105392841B
Low-water absorption high-rigidity nylon composite material and preparation method thereof
CN104262957A
Heat-conducting antistatic environment-friendly flame-retardant high-temperature-resistant nylon composite and preparation method thereof
CN106867244A